Discontinuous Galerkin FEMs for Radiation Transport Problems - Widdowson, Richard (2023)
The linear Boltzmann transport equation (LBTE), a high dimensional partial integrodifferential equation, is used to model radiation transport. Radiation transport is an area of physics that is concerned with the propagation and distribution of radiative particles, such as photons and electrons within a material medium.